Psychometric Properties of the Chinese Version of the Brief-Mindful Self-Care Scale: A Translation and Validation Study - Yang, Zhen; Chen, Fengmin; Liu, Siqi; Dai, Ming; Zhang, Huijun (Frontiers in Psychology, 2021)
Objective: This study aimed to translate the Brief-Mindful Self-Care Scale (B-MSCS) into Chinese and validate its reliability and validity among hospice nurses. Methods: A total of 510 hospice nurses were recruited from three provinces in China. The reliability of the translated scale was measured by internal consistency, split-half reliability, and test-retest reliability. The validity of the translated scale was evaluated by expert consultation, exploratory factor analysis and confirmatory factor analysis. Results: The Cronbach's α value of the Chinese version of B-MSCS was 0.920, and the Cronbach's α value of the dimensions ranged from 0.850 to 0.933. The split-half reliability and test-retest reliability were 0.770 and 0.723, respectively. Furthermore, the content validity index of the scale (S-CVI) was 0.946. The 6-factor structure, supported by the eigenvalues, total variance explained, and scree plot were obtained by using exploratory factor analysis. Moreover, as a result of the confirmatory factor analysis, the model fitting indexes were all in the acceptable range. Conclusion: The Chinese version of B-MSCS had suitable reliability and validity among hospice nurses. The developed scale will evaluate the level of mindful self-care of Chinese hospice nurses, providing an opportunity for development of targeted educational plans. Each item is a direct guide for hospice nurses to develop their mindful self-care practice.